The Role of Information and Communication Technology in Increasing Awareness and Practice of Healthy Nutrition in the Community - Yoanita Hijriyati; Agnes Ratna Saputri; Putri Erlyn; Ni Nyoman Murti; Rufidah Maulina (CV. Get Press Indonesia, 2024)
Nutritional problems remain a serious challenge in global public health, including in Indonesia. Malnutrition and unbalanced nutritional consumption often contribute to various health problems, such as stunting in children, obesity, and non-communicable diseases such as diabetes and hypertension.The Internet, social media, health apps, and other digital tools provide opportunities to inform the public about the importance of proper nutrition and offer practical strategies for adopting healthy eating patterns.This study aims to explore the role of ICT in improving community nutrition awareness and practices, and to analyze how the use of technology can support nutrition interventions more effectively.This study uses a quantitative approach. The qualitative approach was used to gain a deeper understanding of the experiences, perceptions, and barriers experienced by the community and health workers in using ICT for nutrition education.The sample of this study included 10 respondents for the quantitative part, which were divided into 5 treatment groups and 5 control groups. The study was conducted at the Batang Kuranji Health Center which was implemented in June 2024. The results in both groups before the provision of educational media tended to be lower in the control group (infographics) and the treatment group (web), with a comparison of poor attitude results of 60%-40%. Community attitudes towards the use of IT in improving nutrition practices showed varied responses.